El ombudsman militar: conflictos entre derechos ciudadanos y orden castrense en la Argentina del Siglo XX / The military ombudsman: conflicts between rights citizens and military order in the Argentina of the 21st Century - Soprano, Germán (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.16905 Trabalho enviado em 25 de novembro de 2014. Aceito em 15 de março de 2015. <p class="Paragraph SCX187716310" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Resumen <p class="Paragraph SCX187716310" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX187716310" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Este trabajo analiza los proyectos de ley presentados en el Congreso Nacional en Argentina, entre 2008 y 2011, creando el instituto del ombudsman militar, o bien proyectando la jurisdicción y competencias de la Defensoría del Pueblo de la Nación a la esfera de la defensa. Comprendiendo este corpus de proyectos, nos interesa reflexionar sobre los conflictos producidos entre, por un lado, la ampliación de los derechos y garantías del personal militar como ciudadanos en democracia y, por otro lado, las concepciones tradicionales acerca del orden, la jerarquía, la disciplina y el ejercicio del mando en las organizaciones castrenses. <p class="Paragraph SCX187716310" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 47px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX187716310" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Palabras clave: ombudsman / militares / derechos ciudadanos / orden militar / Argentina siglo XXI Abstract: This paper analyzes the bills presented in the National Congress in Argentina between 2008 and 2011, creating the institute of the military ombudsman, either projecting the jurisdiction and powers of the Ombudsman of the People of the Nation to the sphere of defense. Understanding this corpus of projects, we want to reflect on conflicts produced between, on the one hand, the expansion of rights and guarantees of military personnel as citizens in a democracy and, on the other hand, the traditional conceptions about the order, hierarchy, the discipline and the exercise of command in military organizations. Keywords: ombudsman / military / rights citizens / military order / Argentina 21st century